2013
DOI: 10.1111/jfpp.12177
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Parameters of the “Fuerte” Avocado When Refrigerated in Different Modified Atmospheres

Abstract: The objective of this work was to evaluate the refrigerated “Fuerte” avocados stored in different modified active atmospheres. The fruits were wrapped in bags made of nylon plus polyethylene and submitted to the following atmospheres: (I) mixture of ambient gases (0.03% CO2 and 21.0% O2); (II) 5.0% CO2 and 4.0% O2; (III) 6.0% CO2 and 4.0% O2; (IV) 7.0% CO2 and 4.0% O2; and (V) 8.0% CO2 and 4.0% O2. The bags containing the fruits were stored at 10C ± 1 and 90 ± 5% relative humidity for 25 days and were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…In general, "Fuerte" avocados under CA, and especially under 1-MCP application, had lower respiratory rates than fruit stored under RA, especially fruit harvested at an earlier maturity stage, at both storage time (30 and 50 d) ( Table 2). A similar effect was also observed by Russo [2] in "Fuerte" when stored in modified atmosphere packaging with 6% CO 2 and 4% O 2 , the same gas levels used in our study. Under RA storage, "Edranol" avocado showed an increase in respiration rate as storage time progressed (Table 3).…”
Section: Ethylene Production and Respiration Ratessupporting
confidence: 90%
See 2 more Smart Citations
“…In general, "Fuerte" avocados under CA, and especially under 1-MCP application, had lower respiratory rates than fruit stored under RA, especially fruit harvested at an earlier maturity stage, at both storage time (30 and 50 d) ( Table 2). A similar effect was also observed by Russo [2] in "Fuerte" when stored in modified atmosphere packaging with 6% CO 2 and 4% O 2 , the same gas levels used in our study. Under RA storage, "Edranol" avocado showed an increase in respiration rate as storage time progressed (Table 3).…”
Section: Ethylene Production and Respiration Ratessupporting
confidence: 90%
“…After 50 d of storage, weight loss increased to higher than 5% in fruit under RA, and lower levels were maintained in fruit under CA or those treated with 1-MCP, which had weight losses of 1.8 and 4.8%, respectively. Russo et al [2] reported similar results in "Fuerte" avocados studying different concentrations of O 2 and CO 2 at low temperature and determined that 7% CO 2 and 4% O 2 were the most effective concentrations for minimizing weight loss. e weight loss in avocado is low under ideal storage conditions with high RH [27].…”
Section: Weight Lossmentioning
confidence: 67%
See 1 more Smart Citation
“…Postharvest weight loss is mainly attributed to perspiration caused by a deficit of steam pressure of the product in relation to its environment [22]. Sellamuthu et al [23] found that weight loss decreased by applying thyme oil vapour and packaging of avocados from different cultivars in modified atmosphere and Russo et al [24] observed that the firmness of the fruits decreased during storage from the fifth day in avocado fruits stored in different atmospheres (CO 2 /O 2 ). Maftoonazad and Ramaswamy [15] applied a coating based on methylcellulose in avocado fruits, observing that coated treatments managed to maintain avocado firmness, which indicates that the use of a nanoemulsion as a coating is an effective alternative to prevent loss of firmness…”
Section: Discussionmentioning
confidence: 99%
“…Higher pH values can be associated with the conversion of organic acids and other complex molecules present in fruits into sugars, which is a source of energy reserve used in the metabolic processes during ripening [24,25]. Saucedo-Pompa et al [26] coated avocado fruits with candelilla wax and ellagic acid and found that the fruits that were not coated had pH values closer to neutrality compared with the other treatments.…”
Section: Discussionmentioning
confidence: 99%